Income Inequality in Society: A Comprehensive Study of Solutions from an Islamic Economic Perspective - tanjung, elpinia; Rukiah; Batubara, Sarmiana (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2024)
Income inequality and poverty are still serious problems in Indonesia's economic development. The Islamic economic approach offers a comprehensive solution through the optimization of social instruments such as zakat, infaq, and waqf. This study discusses the great potential of zakat and waqf in Indonesia in the context of poverty alleviation and equitable distribution of welfare. Based on data from the National Amil Zakat Agency (BAZNAS) and the Indonesian Waqf Agency (BWI), the potential for national zakat reaches more than IDR 300 trillion per year, while the potential for money waqf is estimated at up to IDR 180 trillion. Although the realization of the collection is still far from this figure, various programs such as Zakatpreneur, educational scholarships, free health services, and productive waqf have made a real contribution in improving the standard of living of the mustahik and strengthening the microeconomic sector. This study emphasizes that structured, professional, and sustainable management of Islamic social funds can be an important pillar in suppressing social inequality and accelerating the achievement of people's welfare. Strategic collaboration between the government, zakat, and waqf management institutions, as well as active participation of the community, is needed to realize this potential to the maximum.